How Effective Are Palm-Fiber-Based Erosion Control Blankets (ECB) against Natural Rainfall? - Jahja, Mohamad; Mudatstsir, Ali; Supu, Idawati; Arifin, Yayu Indriati; Rauf, Jayanti; Sakakibara, Masayuki; Yamaguchi, Tsutomu; Metaragakusuma, Andi Patiware; Butolo, Ivana (Sustainability, 2024)
Rainfall-induced soil erosion is a significant environmental issue that can lead to soil degradation and loss of vegetation. The estimated global annual loss increased by 2.5% over 11 years, from 35 billion tons in 2001 to 35.9 billion tons in 2012, mainly due to spatial changes. Indonesia is predicted to be among the largest and most intensively eroded regions among countries with higher soil erosion, regarded as hot-spots higher than 20 Mg yr−1 ha−1. Due to climate change, natural rainfall patterns in the tropical regions have been subject to change, with a lower number of rainy days and increased intensity of precipitation. Such changes trigger more soil erosion due to heavier rainfall kicking up dried soil particles that are exposed in the bare embankments. Unfortunately, there is no prevention available in developing countries due to the lack of availability and high prices of mitigation techniques such as terraces and covering areas with geotextiles or blankets. Erosion control blankets (ECBs) have emerged as a potential solution to mitigate soil erosion. This research article aims to evaluate the effectiveness of sugar-palm-fiber-based ECB in reducing soil erosion caused by natural rainfall. The study investigates the effectiveness of sugar-palm-based ECB in protecting against erosion at the designated embankment. During the three months of typical rainy seasons (February to April 2023), total eroded mass (kg) was collected and measured from two adjacent microplots (10 m2 each), one covered with ECB and the other one left as uncovered soil (bare soil). The results indicate that eroded mass is proportional to rainfall, with coefficients of 0.4 and 0.04 for bare soil and ECB-covered embankments, respectively. The total soil loss recorded during the monitoring period was 154.6 kg and 16.7 kg for bare and ECB-covered soil, respectively. The significantly high efficiency of the up to 90% reduction in soil losses was achieved by covering the slope with sugar-palm-fiber-based ECB. The reason for this may be attributed to the intrinsic surface properties of sugar palm fiber ropes and the soil characteristics of the plot area. Sugar palm (Arenga pinnata) fiber has higher lignocellulosic contents that produce a perfect combination of strong mechanical properties (higher tensile strength and young modulus) and a higher resistance to weathering processes. Although the cost of production of handmade sugar-palm-fiber-based ECB is now as high as 4 EUR, further reductions in cost production can be achieved by introducing machinery. Compared to typical ECBs which have smaller openings, sugar-palm-based ECB has larger openings that allow for vegetation to grow and provide it with a lower density. As such, we recommend improvements in the quality of palm-fiber-based ECB via the introduction of further automation in the production process, so that the price can be reduced in line with other commercially available natural fibers such as jute and coir.